Photogrammetry in underground mining ground control — Lucky Friday mine case study - Benton, D.J.; Seymour, J.B.; Boltz, M.S.; Raffaldi, M.J.; Finley, S.A. (Deep Mining 2017: Proceedings of the Eighth International Conference on Deep and High Stress Mining, 2017)
Deformation and support conditions in underground mines are typically monitored through visual inspection and geotechnical instrumentation. However, the subjectivity of visual observation techniques can result in ambiguous or incomplete analyses with little quantifiable data. Monitoring displacements with conventional instrumentation can be expensive and time-consuming, and the information collected is typically limited to just a few locations. Moreover, conventional methods usually provide vector rather than tensor descriptions of geometry changes, the latter of which offer greater insight into rock movements and potential ground fall hazards. To address these issues, researchers from the National Institute for Occupational Safety and Health’s Spokane Mining Research Division have developed and evaluated photogrammetric systems for ground control monitoring applications in underground mines. In cooperation with the Hecla Mining Company, photogrammetric surveys were conducted over a three-year period at the Lucky Friday mine in northern Idaho, United States of America, as underhand cut-and-fill mining methods were used to mine Ag-Pb-Zn ore in rockburst-prone ground conditions at depths approaching 2,100 metres. A photogrammetric system was developed for underground use at the mine that is not only mobile, rugged, and relatively inexpensive, but also capable of producing measurements comparable to conventional displacement-measuring instrumentation. This paper describes the components of the photogrammetric system, discusses the use of point cloud analyses from photogrammetric surveys to monitor bulk deformation in underground entries, and explains the advantages of full tensor descriptions of three-dimensional (3D) ground movement, particularly in regard to the interpretation of potential movement along fault intercepts. The practical use of photogrammetry to augment measurements from conventional instruments, such as crackmeters, is presented, as well as the use of photogrammetric data in conjunction with 3D visualisation software to synthesise and integrate complex information from diverse sources including geology, mining configuration, seismicity, and geotechnical instrumentation.